Strategi Empat Pilar dalam Membangun Brand Awareness pada Portal KalderaNews.com - Johanes Sutanto; Finsensius Yuli Purnama (Calathu: Jurnal Ilmu Komunikasi, 2023)
The use of Integrated Marketing Communication (IMC) has become a necessity during increasing competition and market penetration in today's business environment. One of the trends in applying IMC to build brand awareness is now focused on a new paradigm that is not solely aimed at acquiring new customers, but rather on efforts to build and maintain long-term relationships with customers. This research analyzes how IMC strategies are implemented on the KalderaNews.com website as an effort to build brand awareness. While IMC is commonly applied in profit organizations, the uniqueness of this research lies in how these strategies are implemented in a non-profit news portal focused on education and technology in Indonesia. This research adopts a qualitative approach, specifically descriptive research, and utilizes a case study method. Data is collected through in-depth interviews and document analysis. The research informants include the Editor in Chief of KalderaNews.com, the Social Media Officer of KalderaNews.com, and the Business Development team of KalderaNews.com. The findings of this research reveal that KalderaNews.com focuses its efforts on building brand awareness through the "four-pillar strategy" consisting of Sponsorship, Sales Promotion, Social Media Marketing, and Direct Marketing to optimize financial resources and human capital. Keywords: four-pillar strategy, Integrated Marketing Communication, brand awareness, KalderaNews.com